Dynamics of Decentralization Policy Implementation in Strengthening Public Services in Indonesia - Ani Heryani; Ade Iskandar (Department of Public Administration, 2025)
The decentralization policy in Indonesia has reconfigured the division of authority between the central government and local governments and created new demands on local public service delivery in the context of rapid digitalization. This study analyzes how decentralization, e-government, and big data interact to shape the quality of public services at the subnational level. Using a qualitative approach based on thematic analysis of policy documents, official reports, and previous empirical studies, it maps the institutional and technological conditions that enable or constrain digital transformation in decentralized settings. The findings show that, where supported by adequate local capacity, decentralization combined with e-government applications can increase the efficiency, transparency, and responsiveness of public services, while the use of big data strengthens evidence-based decision-making and innovation in service design, and the study identifies persistent gaps in infrastructure, human resources, and data governance that risk reproducing inequalities between regions and limiting the benefits of digitalization. This article contributes by integrating debates on decentralization, digital governance, and data-driven public management into a single framework that treats decentralization as the institutional context, e-government as the digital infrastructure of service delivery, and big data as the informational infrastructure for decision-making and innovation. It offers guidance for central and local governments to better align decentralization policies, e-government initiatives, and big data strategies in order to build more inclusive, accountable, and data-informed public services in Indonesia.